Higher Serum Lysophosphatidic Acids Predict Left Ventricular Reverse Remodeling in Pediatric Dilated Cardiomyopathy - Wen, Haichu; You, Hongzhao; Li, Yulin; Ma, Ke; Jiao, Meng; Wu, Shaowei; You, Shijie; Huang, Jie; Su, Junwu; Gu, Yan; Wang, Zhiyuan; Zheng, Ping; et al. (Frontiers in Pediatrics, 2021)
Background The prognosis of pediatric dilated cardiomyopathy (PDCM) is highly variable, ranging from death to cardiac function recovery. Left ventricular reverse remodeling (LVRR) represents a favorable prognosis in PDCM. Disturbance of lipid metabolism is associated with the change of cardiac function, but no studies have examined lipidomics data and LVRR. Methods Discovery analyses were based on 540 targeted lipids in an observational, prospective China-AOCC (An Integrative-Omics Study of Cardiomyopathy Patients for Diagnosis and Prognosis in China) study. The OPLS-DA and random forest (RF) analysis were used to screen the candidate lipids. Associations of the candidate lipids were examined in Cox proportional hazards regression models. Furthermore, we developed a risk score comprising the significant lipids, with each attributed a score of 1 when the concentration was above the median. All significant findings were replicated in a validation set of the China-AOCC study. Results There were 59 patients in the discovery set and 24 patients in the validation set. LVRR was observed in 27 patients (32.5%). After adjusting for age, left ventricular ejection fraction (LVEF), and left ventricular end-diastolic dimension (LVEDD) z-score, LysoPA 16:0, LysoPA 18:2, LysoPA 18:1, and LysoPA 18:0 was significantly associated with LVRR in the discovery set and hazard ratios were 2.793 (95% CI, 1.545-5.048), 2.812 (95% CI, 1.542-5.128), 2.831 (95% CI, 1.555-5.154) and 2.782 (95% CI, 1.548-5.002), respectively. We developed a LysoPA score comprising the four LysoPA. When the LysoPA score reached 4, LVRR was more likely to be observed in both sets. The AUC increased with the addition of the LysoPA score to the LVEDD z-score (from 0.693 to 0.875 in the discovery set, from 0.708 to 0.854 in the validation set) for prediction of LVRR. Conclusions Serum LysoPA can predict LVRR in PDCM patients. When the LysoPA score was combined with the LVEDD z-score, it may help for ascertaining the prognosis and monitoring effects of anti-heart failure pharmacotherapy.